2005
DOI: 10.1017/s135561770505068x
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting patient/informant discrepancies of reported cognitive symptoms in MS

Abstract: Although numerous studies have shown that brain-damaged patients tend to underestimate neuropsychological (NP) impairment when self-ratings are compared to informant ratings, the meaning of such discrepancies is not well studied in multiple sclerosis (MS). We compared patient self- and informant-report questionnaire ratings of NP functioning in 122 MS patients and 37 age- and education-matched normal controls. In addition to completing the Multiple Sclerosis Neuropsychological Questionnaire (MSNQ), participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
94
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 65 publications
14
94
2
1
Order By: Relevance
“…These findings could also be viewed as extending the "depressive realism" (Dunning and Story, 1991) and "sadder but wiser" (Alloy and Abramson, 1979) concepts to a psychotic population. Additionally, these findings are similar to previous studies of multiple sclerosis patients, which also found higher depression in those who underestimated their cognitive ability (Carone et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings could also be viewed as extending the "depressive realism" (Dunning and Story, 1991) and "sadder but wiser" (Alloy and Abramson, 1979) concepts to a psychotic population. Additionally, these findings are similar to previous studies of multiple sclerosis patients, which also found higher depression in those who underestimated their cognitive ability (Carone et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Lack of convergence between self-reported cognitive and functional impairments and information collected from outside observers is not limited to schizophrenia. In fact, patients with traumatic brain injuries (Hoofien et al, 2004) and conditions such as multiple sclerosis (Carone et al, 2005) have also been reported to produce appraisals of their functional and cognitive capabilities that were discrepant from objective performance and informant ratings. Interestingly, in both illnesses, the presence of depression was associated with accurate to underestimated reports of cognitive and functional skills, while greater cognitive impairments and emotional lability were found to correlate with overestimation of performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors have suggested a relationship between MC and emotional distress in patients with epilepsy (5-16) and similar results have been found in general medical conditions (25)(26)(27)(28). The novelty of this study is the delineation of MC in a large sample of patients with epilepsy using user-friendly standardised clinical instruments which can be adopted in any outpatient clinic in a real life setting.…”
Section: Discussionsupporting
confidence: 74%
“…27,30 There is better agreement between NP testing and informant-reported MSNQ data, although not to the degree that one can use the MSNQ to screen for NP impairment with sufficient sensitivity and specificity. While the MSNQ is considered reliable, providing interesting data with regard to indifference and depression pseudo-dementia, 26 several studies show that self-reported scales focusing on cognition are mostly related to depression, not cognitive capacity. 28,29,31 Thus, it would be difficult, if not impossible, to supplant a performance-based measure of cognition with a self-reported assessment, nor to use self-assessments as anchors for interpretability.…”
Section: Self-reports Are Not Valid Anchors For Cognitive Outcomesmentioning
confidence: 99%